2019
DOI: 10.1002/hpm.2732
|View full text |Cite
|
Sign up to set email alerts
|

Do corporate governance mechanisms and internal control systems matter in reducing mortality rates?

Abstract: Summary Internal controls are critical to guarding an institution against fraud, error, and devastation. They are effective tools for preventing losses and achieving organizational goals. However, internal control mechanisms need to be relevant, because the organization cannot comprehend the effectiveness of the system if they are out‐of‐touch with the operation. Health care control practices are not exceptionally different from what pertains in other industries. The health care organizations require effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Previous studies have confirmed that the regulatory effectiveness of external media and government departments (Yang and Zhao, 2017; Mei, 2018; Xiong et al , 2018; Yin and Li, 2018), analyst tracking (Chen et al , 2016), the level of internal governance (Liang et al , 2004; Chen et al , 2016; Afriyie et al , 2019), the ownership structure (Fan and Wong, 2002; Lu et al , 2012; Afriyie et al , 2019) and pay incentive policies (Johnson et al , 2009; Zhang and Zhang, 2017; Wei and Geng, 2018) can provide potential opportunities for violations. As an important component of the internal corporate governance system, the restraining effect of the quality of the internal audit function on the quality of corporate financial reporting has been widely recognized (Altamuro and Beatty, 2010; Wang et al , 2010; Shi et al , 2011; Gros et al , 2017).…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies have confirmed that the regulatory effectiveness of external media and government departments (Yang and Zhao, 2017; Mei, 2018; Xiong et al , 2018; Yin and Li, 2018), analyst tracking (Chen et al , 2016), the level of internal governance (Liang et al , 2004; Chen et al , 2016; Afriyie et al , 2019), the ownership structure (Fan and Wong, 2002; Lu et al , 2012; Afriyie et al , 2019) and pay incentive policies (Johnson et al , 2009; Zhang and Zhang, 2017; Wei and Geng, 2018) can provide potential opportunities for violations. As an important component of the internal corporate governance system, the restraining effect of the quality of the internal audit function on the quality of corporate financial reporting has been widely recognized (Altamuro and Beatty, 2010; Wang et al , 2010; Shi et al , 2011; Gros et al , 2017).…”
Section: Introductionmentioning
confidence: 90%
“…This commitment materializes in respect of stakeholders, transparency, effective management by the administrative team, the auditing of outcomes and good communication. When applied in hospitals, this model has been shown to help prevent financial losses and reduce mortality (Afriyie et al, 2019). For our purposes, nurses can be considered a stakeholder group, both because they belong to the same society as the people they care for and because the enterprise cannot survive without them (He, 2011).…”
Section: Dimensions Of Nursing Governance In Intermediate Carementioning
confidence: 99%
“…When transparency and communication are lacking, problems of trust can ensue (Alimehmeti & Paletta, 2014). Having a communication strategy that includes transparency (e.g., by using simple messaging) improves health outcomes, increases patient satisfaction, encourages joint problem‐solving and makes it easier to align personal and organisational goals (Afriyie et al, 2019).…”
Section: Dimensions Of Nursing Governance In Intermediate Carementioning
confidence: 99%
“…De acuerdo con lo expuesto, el incumplimiento de las obligaciones de pagos de los individuos está ligado a situación económica, es por ello que la máxima autoridad en conjunto con los mandos medios deben medir el grado de eficiencia, eficacia y economía en la gestión de recuperación de cartera vencida a fin de minimizar el riesgo financiero y evitar el alto índice de morosidad para garantizar el logro de los objetivos e implementar medidas preventivas y correctivas a dichas deficiencias (Afriyie, et al, 2019); (Sy & Tinker, 2019).…”
Section: Extinciónunclassified